2021
DOI: 10.47067/ramss.v4i1.97
|View full text |Cite
|
Sign up to set email alerts
|

As Study on Workplace Ostracism on Work Productive Behavior of Employees With Mediating Effect of Emotional Intelligence

Abstract: Ostracism in the workplace has emerged as the burning issue for organizations, that grabbed the attention of researchers, practitioners and academicians to help corporate world. Thus, every organization is wandering the result-oriented solution to this issue to get employees satisfied and motivated. The research used ostracism as an independent, emotionally intelligence is mediator and counterproductive work behavior, aggressive behavior and workplace deviance as dependent variables. The research is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This finding is matched with (32) who stated that studied nurses have a low level of WPO. These findings are in the same line with (33) who found that half of the studied nurses suffered from low WPO.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is matched with (32) who stated that studied nurses have a low level of WPO. These findings are in the same line with (33) who found that half of the studied nurses suffered from low WPO.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, Zahid et al [51] stated that the studied nurses have a low level of WO. Similarly, Chen and Li [52] and Armstrong [53] found that more than half of the staff nurses had a low level of WO, while a minority of them had a high level of workplace ostracism.…”
Section: Discussionmentioning
confidence: 93%
“…First, we explored the relation of perceived supervisor support on employee proactive behavior and expanded the exploration of antecedent variables of employee proactive behavior. Previous studies mainly explored the antecedents of employee behavior, especially proactive behavior, from negative factors such as workplace ostracism ( Zhao et al, 2013 ; Gürlek, 2021 ; Zahid et al, 2021 ; Zhou et al, 2021 ). In the context of COVID-19, the popularity and promotion of working from home has brought a series of problems to employees, such as conflicts between work and family roles.…”
Section: Discussionmentioning
confidence: 99%